2023
DOI: 10.1111/pcn.13578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of education regarding treatment guidelines for schizophrenia and depression on the treatment behavior of psychiatrists: A multicenter study

Naomi Hasegawa,
Yuka Yasuda,
Norio Yasui‐Furukori
et al.

Abstract: AimThis study aims to examine the real‐world effectiveness of education regarding clinical guidelines for psychiatric disorders using ‘the Effectiveness of guidelines for dissemination and education in psychiatric treatment (EGUIDE)’ project.MethodsThe EGUIDE project is a nationwide prospective implementation study of two clinical practice guidelines, i.e., the Guideline for Pharmacological Therapy of Schizophrenia and the Treatment Guidelines for Major Depressive Disorders, in Japan. Between 2016 and 2019, 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…First, postgraduate education for psychiatrists working at the front line of treatment on basic medical treatment methods and treatment techniques for psychiatric patients with sleep problems is considered an important option to promote behavioral change among psychiatrists. It has been previously reported that participation in the EGUIDE project increased psychiatrists' expertise and changed their practice behavior [ 7 , 9 , 10 ]. The second method is to provide more specialized sleep treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, postgraduate education for psychiatrists working at the front line of treatment on basic medical treatment methods and treatment techniques for psychiatric patients with sleep problems is considered an important option to promote behavioral change among psychiatrists. It has been previously reported that participation in the EGUIDE project increased psychiatrists' expertise and changed their practice behavior [ 7 , 9 , 10 ]. The second method is to provide more specialized sleep treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These patient data were divided into two groups: patients treated by psychiatrists participating in the EGUIDE project (EGUIDE ( +)) and patients treated by psychiatrists not participating in the EGUIDE project (EGUIDE (-)), as described in a previous study. If both EGUIDE ( +) and EGUIDE (-) patients were assigned to the same patient, they were assigned to the EGUIDE ( +) group [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations